US' Section 301 actions: Why they are illegitimate and misguided - Aileen Kwa; Peter Lunenborg (South Centre, 2018)
This research paper examines the US' Section 301 unilateral actions against China, stemming from the US' concerns over China's ambitious industrial policies and its rapid technological advancements. It outlines the accusations of the US regarding China's conditions for technology transfer and what the US sees as overly intrusive Chinese government involvement in investments. It looks in detail at why the US' actions are in fact illegitimate and misguided. Most of the US' accusations are not framed by WTO rules. Furthermore, the US cannot unilaterally take action that contravenes another WTO Member's rights under WTO agreements without going through the WTO's Dispute Settlement Body. Most strikingly, the US is accusing China of industrial policies and for supporting its companies to move up the technological ladder while it has been the pre-eminent country having its own version of such policies including until today. If these actions continue and expand, the ensuing trade war is likely to delegitimize the WTO and its current functions in regulating trade, lead to economic slow-down, and even possibly financial crises in emerging economies.
Keywords: 300; WTO-Recht; Handelskonflikt; Technologietransfer; Internationale Schiedsgerichtsbarkeit; USA; China